Self-Fulfilling Fire Sales: Fragility of Collateralized Short-Term Debt Markets - Kuong, John Chi-Fong (Review of Financial Studies, 2021)
This paper shows that collateralized short-term debt, although privately optimal for reducing borrowers’ risk-taking incentives, can induce fragility (multiple equilibria). Despite sequential-service property being absent in collateralized debt, such as repurchase agreements, a systemic run can arise, featuring large increases in default risks, fire-sale discounts of collateral, cost of credit, and amount of credit rationing. Asset price guarantees, leverage caps, and central clearing promote stability and welfare. Using global games techniques, I show that a systemic run is more likely in bad times, and a large enough asset price guarantee reduces run risks.